Linking forest management and biodiversity indicators to strengthen sustainable forest management in Europe. (March 2021) - Oettel, Janine; Lapin, Katharina
Highlights: Our review linked 44 biodiversity indicators with 32 forest management indicators. Arthropods, birds, and plants are the most frequently used biodiversity indicators. 14 Forest management measures were defined to influence biodiversity indicators. We identified 17 umbrella species, but clear thresholds for forest management are still missing. Measures related to deadwood, stand structure and management intensity affect biodiversity most. Abstract: The accelerating global rate of species extinctions and the inevitable human impacts on biodiversity have increased the need to conserve, restore and use ecosystems sustainably. Indicators for biodiversity are the most frequently used tool to monitor the status of biodiversity, changes to biodiversity, and the effects of management actions. In this study, we aim to assess the magnitude of studies on indicators for biodiversity (IB) in European forest ecosystems, establish and analyze the link between IB and silvicultural management measures (MM), and define indicators for management (IM), that aim to support biodiversity at the stand and landscape level. We performed a systematic literature review and analyzed data from 162 studies. We identified 9 IB groups, corresponding to 32 IB and linked them to 7 IM groups corresponding to 44 IM. Arthropods, birds, and plants are the most frequently used IB in European managed forests. We found IB with clear links to specific IM, such as saproxylic species and Collembola (collembolans) with deadwood, bird families (Passeriformes, Piciformes, Accipitriformes) with links to microhabitats, and ground-dwelling species with links to regeneration. We identified 17 species as proposed umbrella species based on the studies examined. This review shows that high structural diversity is associated with an increase in diversity, especially with regard to vascular plants, birds and ground-dwelling species. The adaptation of forest management for biodiversity requires regular active monitoring of IM to assess the temporal and spatial changes and of IB to assess the effectiveness of measures.